Genetic variability of Triatoma rubrovaria (Reduviidae: Triatominae) from Brazil, Argentina and Uruguay as revealed by two different molecular markers - Pacheco R.S.; Almeida C.E.; Klisiowicz D.R.; Costa J.; Pires M.Q.; Panzera F.; Bar M.E.; Mas-Coma S.; Bargues M.D. (Parasite, 2007)
Randomly amplified polymorphic DNA (RAPD) and nuclear ribosomal DNA sequence analyses were used to assess the genetic population structure of the South American triatomine species Triatoma rubrovaria throughout its geographical distribution. To investigate the genetic variability at both intraspecific and intrapopulational levels the RAPD profiles and the nucleotide sequences of the rDNA intergenic spacers, ITS-1 and ITS-2, were analysed and compared. The phenetic analysis based on RAPD profiles show three distinct clusters diverging by similarity coefficients ranging from 0.62 to 0.96. The ITS-1 and ITS-2 sequence variability detected may be considered very high, suggesting reproductive isolation between populations. A total of seven composite haplotypes (CH) were found, among which three are specific for Brazil, other three for Uruguay, and the last one common for the three countries studied. The population studied in Argentina does not represent an independent CH. Sequence analyses proved that the five populations studied are easily differentiable and that there is heterogeneity within each one. True mutations and indels are the responsible of sequence differences between haplotypes and populations, suggesting that divergence processes may presently go on within this species. The large intraspecific variability detected may underlie the known plasticity of T. rubrovaria, making it a potential intradomiciliary invader and consequently an appropriate vector for Chagas disease transmission. Therefore, this triatomine species must be continuously monitored throughout.